Concentration of phase-information - Usuga, Mario; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Andersen, Ulrik L.A.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2010)
We demonstrate a probabilistic scheme capable of increasing the phase information of weak coherent states by addition of thermal noise and subsequent photon-counting based postselection. We present experimental and theoretical results. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05